2018
DOI: 10.1155/2018/8620172
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Limbal Epithelial Stem Cells in Regulating Corneal (Lymph)angiogenic Privilege and the Micromilieu of the Limbal Niche following UV Exposure

Abstract: The cornea is a clear structure, void of blood, and lymphatic vessels, functioning as our window to the world. Limbal epithelial stem cells, occupying the area between avascular cornea and vascularized conjunctiva, have been implicated in tissue border maintenance, preventing conjunctivalisation and propagation of blood and lymphatic vessels into the cornea. Defects in limbal epithelial stem cells are linked to corneal neovascularisation, including lymphangiogenesis, chronic inflammation, conjunctivalisation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 138 publications
(177 reference statements)
1
61
0
1
Order By: Relevance
“…At days 7, 14, 21, and 28 after injury, the cornea was serially observed for clinical signs of LSCD: corneal epithelial defects, vascularization, and opacification (Fig. A) . Rapamycin treatment significantly delayed corneal epithelial healing in a dose‐dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At days 7, 14, 21, and 28 after injury, the cornea was serially observed for clinical signs of LSCD: corneal epithelial defects, vascularization, and opacification (Fig. A) . Rapamycin treatment significantly delayed corneal epithelial healing in a dose‐dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the failure of CESCs to regenerate corneal epithelial cells leads to corneal opacification and severe visual impairment, a condition called limbal stem cell deficiency (LSCD) . Although various diseases of the cornea can produce LSCD, the most severe form of LSCD is associated with sterile inflammation as in chemical burn or Stevens–Johnson syndrome, an indication that inflammatory damage underlies the loss of CESCs in LSCD . For this reason, the current treatment options for LSCD include anti‐inflammatory therapies such as corticosteroids or amniotic membrane transplantation in the acute phase of a disease.…”
Section: Introductionmentioning
confidence: 99%
“…Isoforms of VEGF-A have differences in the affinities for heparan sulfate proteoglycans (HSPGs) and VEGF receptors, which exert distinct influences on vessel growth. VEGF-A binds to two tyrosine kinases, vascular endothelial growth factor receptor-1 (VEGFR-1) and vascular endothelial growth factor receptor-2 (VEGFR-2) in high affinity, and receptors are abundant in vascular endothelial cells (Notara, Lentzsch, Coroneo, & Cursiefen, 2018). These effects like permeability, migration, and proliferation are achieved by signal pathways, such as MAPK, NO, and PI-3K-AKT/PKB (Penn et al, 2008).…”
Section: Vegf Pathwaymentioning
confidence: 99%
“…Many studies reported that the limbal region functions as a barrier between the cornea and conjunctiva. The role of the barrier is to block the conjunctivalization and the neovascularization of the cornea [10][11][12][13]. Damage to this barrier leads to the development of limbal stem cell deficiency (LSCD).…”
Section: Introductionmentioning
confidence: 99%